2022
DOI: 10.3390/foods11040531
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Properties and Main Differential Metabolites Influencing the Taste Quality of Dry-Cured Beef during Processing

Abstract: This study adopted widely targeted high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) metabolomics and multivariate data analysis methods to evaluate the correlation between changes in metabolites and their taste formation in dry-cured beef during processing. The physicochemical profile changed significantly in the maturity period (RG), especially due to the continuous hydrolysis and oxidation of proteins. The sensory characteristic of dry-cured beef was highest in saltiness, umami, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
1
7
2
Order By: Relevance
“…Previous studies have reported that amino acid derivatives and nucleotide derivatives are abundant metabolites in dry-cured meat products. 17,26 In the present study, although N-acetylmethionine and N-acetyllysine showed a high concentration (258.62 ng g −1 and 301.29 ng g −1 , respectively) in SX&SV, the high taste threshold (> 2000 μmol L −1 ) of them decreased their contributions to the taste of dry-cured bacon. 17 Similarly, IMP and AMP also had a high wileyonlinelibrary.com/jsfa taste threshold (2500 and 4000 μmol L −1 , respectively) and a very low concentration (12.91 and 23.15 ng g −1 , respectively).…”
Section: Changes In Sensory Evaluationcontrasting
confidence: 50%
See 3 more Smart Citations
“…Previous studies have reported that amino acid derivatives and nucleotide derivatives are abundant metabolites in dry-cured meat products. 17,26 In the present study, although N-acetylmethionine and N-acetyllysine showed a high concentration (258.62 ng g −1 and 301.29 ng g −1 , respectively) in SX&SV, the high taste threshold (> 2000 μmol L −1 ) of them decreased their contributions to the taste of dry-cured bacon. 17 Similarly, IMP and AMP also had a high wileyonlinelibrary.com/jsfa taste threshold (2500 and 4000 μmol L −1 , respectively) and a very low concentration (12.91 and 23.15 ng g −1 , respectively).…”
Section: Changes In Sensory Evaluationcontrasting
confidence: 50%
“…This finding was supported by the obvious increase in the content of 5′‐GMP, adenosine and guanosine in SX&SV. In the presence of benzoyl‐CoA reductase, apyrase and GMP reductase, ATP was reduced to ADP and subsequent reduction to 5′‐AMP and 5′‐GMP 26 . Moreover, the TCA cycle was also changed in SX&SV and the observed increase in the content of 4‐guanidinobutanoic acid provided evidence for this finding.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The addition of IMP to sweet amino acids also has the effect of enhancing sweetness [ 22 ]. GMP is considered an important flavor substance of dried mushrooms [ 23 ]. At the same time, these taste nucleotides can produce synergistic effects with ASP, Glu, etc., to produce a stronger flavor effect.…”
Section: Resultsmentioning
confidence: 99%